investigasi pengalaman guru non jurusan bahasa inggris dalam mengajar bahasa inggris - Kuni Zakiyatul Hamidah; Durratul Hikmah (Journal Of Language Education and Development (JLed), 2025)
English is a compulsory subject in junior high schools, yet many institutions, including Islamic boarding schools (pesantren), rely on non-English teachers due to limited qualified staff. This study aims to investigate the experiences of non-English teachers in teaching English at MTs Nurul Jadid, focusing on the challenges faced and the strategies implemented to improve student comprehension. Using a qualitative phenomenological design with interviews and observations, the study found that the main challenges were student fatigue due to intensive Islamic boarding school activities and low learning motivation. Teachers addressed these challenges through adaptive classroom management, contextual and interactive learning, and continuous self-development. These findings highlight that with commitment, professional awareness, and adaptability, non-English teachers can teach English effectively in an Islamic boarding school context.